ATP-sensitive K-channels in HIT T15 beta-cells studied by patch-clamp methods, 86Rb efflux and glibenclamide binding. - Niki, I; Kelly, R; Ashcroft, S; Ashcroft, F (Springer-Verlag, 1989)
ATP-sensitive K-channels in the cloned beta-cell line HIT T15 were studied by patch-clamp methods; by measurement of 86Rb efflux; and by [3H]glibenclamide binding to isolated membrane preparations. In inside-out patches a 50 pS K-channel was found which was blocked by ATP or tolbutamide applied to the intracellular membrane surface. A minimum estimate of about 500 channels per beta-cell was obtained by combining whole-cell and single-channel data. The rate of efflux of 86Rb from 86RbCl-loaded HIT cells was markedly increased by intracellular ATP-depletion; 86Rb-efflux was progressively inhibited by increasing concentrations of glibenclamide or tolbutamide. In non-ATP-depleted cells, diazoxide elicited a concentration-dependent stimulation of 86Rb-efflux which was completely blocked by 1 microM glibenclamide. Isolated membranes showed dose-dependent saturable binding of [3H]glibenclamide to both high (Kd = 1.12 nM) and low (Kd = 136 nM) affinity binding sites. We estimate about 5000 high-affinity binding sites per cell. [3H]-glibenclamide binding was inhibited by tolbutamide (IC50 = 125 microM) but was not affected by diazoxide. ADP (0.5 or 1.0 mM) markedly reduced binding; other nucleotides tested were ineffective.